Haiti’s “Painful Truths”: A Postcolonialised Reading of Trauma in Roxane Gay’s An Untamed State - Roldán-Sevillano, Laura (ES review (Internet), 2022)
Drawing on a postcolonialised approach to the traditional trauma paradigm, this paper analyses Roxane Gay’s novel An Untamed State as a trauma narrative which does not solely revolve around the Haitian American protagonist’s Post-Traumatic Stress Disorder ensuing her abduction and violation in Port-au-Prince, as suggested by previous critical work. Particularly, it aims to demonstrate that Gay’s heroine is a resilient survivor of both a rape-related trauma and the traumatic blow to her partly Haitian identity caused by her direct contact with Haiti’s social and gender issues. Lastly, the essay examines how the novel delves into the unresolved cultural traumas derived from the effects of (post)colonialism in Haiti, which push the protagonist’s victimisers to commit such terrible acts.